Probing conducting interfaces by combined photoluminescence and transport measurements: LaVO 3 and SrTiO 3 interface as a case study - De, Joydip; Pal, Santanu Kumar (APS, 2021)
The carrier-density distribution near a conducting interface and the related band structure are topics of great contemporary importance in low-dimensional quantum solids. We propose a scheme, innovatively combining the spectroscopy techniques of photoluminescence and time-correlated single-photon counting with transport measurements of resistivity to unravel the carrier distribution, the shape of quantum well, energy subbands, and Fermi surfaces of the conducting interface of LaVO 3 and SrTiO 3 . Electronic parameters, such as the carrier density, the mobility, estimated from the electrical measurements, are in remarkably good agreement with those extracted from the spectroscopy with theoretical modeling providing a bridge between the two sets of data analysis.
Only IISERM authors are available in the record
Keywords: Hall effect; Photon counting